Model-Based Fuzzy Control Results for Networked Control Systems (Reports in Mechanical Engineering, 2020)
This paper discusses aspects concerning the design of model-based fuzzy controllers for Networked Control Systems (NCSs). The stability analysis is related to the characteristic equation of these control systems, where the variable time delays create numerical problems. These numerical problems are first briefly investigated, along with signal processing aspects concerning NCSs. The popular Hilbert-Huang transform is applied to smooth the signals and also the variable time delay, also called latency, due to the communication in the network. The design of Takagi-Sugeno-Kang Proportional-Integral-fuzzy controllers dedicated to temperature control applications is next carried out; the stability of fuzzy NCSs is guaranteed by computing the controller tuning parameters as solutions to linear matrix inequalities. Experimental results for a laboratory equipment that models a first-order plus time delay process are included to validate the theoretical findings.